Transformation of Innovation Infrastructure in the Conditions of Organizational Changes in Russia - Gnezdova, Julia Vladimirovna; Kuzin, Dmitry Vladimirovich; Manyushis, Algirdas Juozovich; Filkevich, Igor Aleksandrovich; Yunusov, Lenar Albertovich (International Journal of Economics and Financial Issues, 2016)
The article deals with topical issues of formation of an innovative infrastructure as a priority direction of the state policy in order to achieve a global level in creating competitive engineering production, agricultural technology, development of architecture, science, engineering, economics, improving welfare and culture through the operational development and enhancement of scientific, technical and intellectual potential in the country. Today the focus is on the innovation economy, which is understood as the economy of society based on knowledge, innovation, benevolent perception of new ideas, machines, systems and technologies, readiness of their implementation in the various areas of human activity. It highlights the special role of knowledge and innovation, especially scientific knowledge. Keywords: Innovation infrastructure, human capital, global innovation index, innovation metrics. JEL Classifications: E22, F01, G10